Penguatan Kemampuan Berpikir Kritis dan Literasi Numerasi melalui Problem Based Learning pada Pembelajaran Matematika SD - Made Sri Astika Dewi; Gusti Ayu Adi Putri Rahayu; Gusti Ayu Ketut Alit Dewi Saputri; Gusti Made Ngurah Saka Wiratama; Luh Putri Diah Dharmayanti; Ni Kadek Ayu Febri Padmawati; Ni Putu Ayu Vania Candra Ulandari (Jurnal Sosial Humaniora dan Pendidikan, 2026)
: This Society 5.0, study seeks examine how PBL paradigm in primary school math education improves pupils' analytical thinking and numeric literacy. Twenty scholarly publications published between 2021 and 2025 that satisfied the criteria set forth by SINTA 1-3 formed the basis of our Systematic Literature Review, which we used to inform our research. Students' analytical and quantitative literacy, along with their general knowledge and skill sets, may be enhanced via (PBL), according to the findings. According to the study, 55% of the total is attributed to critical thinking abilities, 25% to numeracy literacy, 15% to learning outcomes, and 5% to PBL implementation and trends. The research concluded (PBL) might be an effective way to introduce primary school pupils to mathematics as it can help them develop skills that are relevant to today's environment and get them more involved in the Society 5.0 age.